Estudos pré-clínicos da atividade antiproliferativa e toxicológica da fração e de diterpenos clerodânicos isolados das folhas da planta Casearia sylvestris Swartz - Ferreira, Paulo Michel Pinheiro (2010)
Among all antitumor molecules available between 1940 and 2002, 40 % has natural origin. However, most of the clinically used antineoplasic compounds lead to adverse effects due to a therapeutic narrow window, pharmacological multiple resistance and morphological and physiological similarities between transformed and normal cells. Given this requirement for the developing of new anticancer drugs, it was initially evaluated the cytotoxic activity of a Fraction rich in Casearinas (FC) and of the diterpen clerodanes casearin B (Cas B), D (Cas D), X (Cas X) e Caseargrewiin F (Cas F) isolated from Casearía sylvestris leaves against a panei of 14 tumor cell lines and on human polymorphic blood mononuclear cells (PBMC). The substances tested were cytotoxic against all lines used, being the Cas F and X the most active compounds. Studies of mechanism of action with Cas B (1 and 2 pM), Cas D (2 and 4 pM), Cas F (0.5 and 1 pM), Cas X (0.7 and 1.5 pM) and FC (0.4 e 0.8 pg/mL) using the HL- 60 leukaemia cell line as experimental model showed DNA synthesis and membrane integrity reduction, DNA fragmentation and mitochondrial depolarization, specially after 24 h exposure, when it was also detected cell cycle arrest in GO/G| phase(Cas X e FC), activation of the initiator -8/-9 and efector -3/-7 caspases and phosphatidylserine externalization, consistent features with apoptosis and corroborated by the chromatinic condensation, karyorrhexis, cytoplasmic vacuolation and rarefaction and cellular shrinkage, morphological findings better observed after 12 and 24 h of incubation. Comet assay in human PBMC revealed that all substances present in vitro genotoxic potential, possessing Cas X the lower DNA damage index. Antitumoral evaluation in mice transplanted with Sarcoma 180 cells showed tumor growth inhibition ratios of 35.8, 86.2 e 53.7 % with doses of FC 10 and 25 mg/kg/day i.p. and 50 mg/kg/day oral by gavage after 7 days of treatment, respectively, though such activity did not elevated the survive time. DL50 values for the i.p. and oral FC were 80.9 e 267.1 mg/kg body weight, respectively. The subcronic injection of the FC for consecutively 30 days in Swiss mice (5 and 10 mg/kg/day) decreased the weight gain, hematocrit, total cholesterol, albumin, glucose and heart relative weight besides causing lymphocytopenia, neutrophilia, hepatosplenomegaly, increased rates of DNA damage in PBMC and in micronuclei formation of bone marrow erythrocytes while oral administration (10 and 20 mg/kg/day) led to enlarged stomach. Both routes of administration caused cell swelling and appearance of inflammatory foci in the parenchyma or stroma liver / kidney, microvesicular steatosis, accumulation of hemosiderin pigments, hyperplasia of Kupffer cells, red pulp congestion and disorder of splenic lymphoid follicles. The largest part of these changes is comparable to the toxicity of traditional cytotoxic chemoterapics and reflects the antiproliferative capacity of the clerodane diterpenes present in FC, emphasizing the potential of these molecules as model for production and/or synthesis of new compounds with anticancer properties.